Impact of elevated urine leukocyte and bacteria count per high-power field on the in-hospital outcome of patients with liver cirrhosis - Han, Dan; Wang, Ran; Yu, Yang; Yang, Sien-Sing; Mueller, Sebastian; Romeiro, Fernando Gomes; Song, Tingxue; Deng, Han; Li, Jing; Peng, Zhong; Li, Yibing; Guo, Xiaozhong; et al. (Journal of Public Health and Emergency; Vol 1 (August 2017): Journal of Public Health and Emergency, 2017)
Background: Liver cirrhosis is prone to the development of urinary tract infection (UTI). Urine culture is a golden standard for the diagnosis of UTI, but it is often missing in routine clinical practice. Urinalysis may be an alternative. This study aimed to evaluate the prevalence of abnormal urinalysis and its impact on the in-hospital outcome of liver cirrhosis. Method: Cirrhotic patients (n=2,067) who were admitted between July 2010 and June 2014 and underwent urinalyses were retrospectively enrolled. A urine leukocyte count of >4.33 and/or a urine bacteria count of >975 per high-power field were defined as abnormal urinalysis. Receiver-operator characteristic (ROC) curve analysis was performed to identify the capacity of urine leukocyte and bacteria count per high-power field for predicting the in-hospital death. The area under the ROC curve (AUROC) was calculated. Results: The prevalence of elevated urine leukocyte and bacteria count per high-power field was 25.8% and 6.7%, respectively. The AUROC of urine leukocyte and bacteria count per high-power field for predicting the in-hospital death were 0.600 (P=0.015) and 0.600 (P=0.014), respectively. The best cut-off value of urine leukocyte per high-power field was 8.19 with a sensitivity of 34.5% and a specificity of 84.8%. The best cut-off value of urine bacteria per high-power field was 142.04 with a sensitivity of 38.6% and a specificity of 84.19%. Conclusions: Abnormal urinalysis is common in liver cirrhosis and may be a predictor for the in-hospital death.